1999
DOI: 10.1002/j.1556-6676.1999.tb02461.x
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Counseling Pioneers: A Visit With Kathleen and Gilbert Wrenn

Abstract: The authors have had the honor of knowing Gilbert and Kathleen Wrenn for 20 years; this story is about them. As Gilbert stated, “I am not a lone star, but part of a constellation… ”(Wachowiak & Aubrey, 1976, p. 76). The authors are privileged to know that for Gilbert, Kathleen (his partner of 72 years in 1996) is the center of that constellation. This article briefly captures pieces of the journey of 72+ years, on which Gilbert and Kathleen, each at 96 years of age, are continuing to travel together.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Among counselor educators, student mentorship was described as a first priority, especially in the context of teaching. Formal programs were also noted as potentially valuable sources of mentorship (e.g., Luke & Goodrich, ; Maples & Maples, ; Portman & Garrett, ).…”
Section: Resultsmentioning
confidence: 99%
“…Among counselor educators, student mentorship was described as a first priority, especially in the context of teaching. Formal programs were also noted as potentially valuable sources of mentorship (e.g., Luke & Goodrich, ; Maples & Maples, ; Portman & Garrett, ).…”
Section: Resultsmentioning
confidence: 99%
“…Vande Kemp, in her review of these historical movements, identified 37 institutions and 17 separate scholarly journals devoted to just such an integration during this century. Finally, articles have recently appeared in the American Counseling Association's Journal of Counseling & Development that review historical and training issues related to religion and spirituality as those issues specifically pertain to counseling care (see Maples & Maples, 1999;Miller, 1999).…”
Section: Integrating Counseling With Religion and Spiritualitymentioning
confidence: 99%
“…By dynamically establishing sensor-to-shooter linkages based upon changing conditions on the battlefield, networked radars will provide the Fires and Effects Cell (FEC) total connectivity to the NLOS battalion. 77 Radars assigned to the UA force structure clearly support the objectives of Joint Vision 2020?Full Spectrum dominance through a highly integrated and rapidly deployable force. As a part of this structure, the UA 21 st century radar will provide 360°c overage for protection and a link to the UE long-range shooters.…”
mentioning
confidence: 92%